PENDEKATAN IJTIHAD TARJI/.LI DALAM AMALAN FATWA JEMAAH ULAMA NEGERI KELANTAN: RUJUKAN KEPADA FATWA-FATWA 1990-AN - Abd Rahman, Noor Naemah (Jurnal Syariah, 2019)
With the cease of the strict and taqlid approach of the Shaft 'i mazhab in the fatwii application in Kelantan, most of the fatwa committee members had chosen to utilize the method of ijtihad tarj[~[ in finding solution to newly arise problems. This article will try to expose the application of such method on several issues that related to the problem faced by the muslim community of Kelantan.